Implementasi Metode Wahdah pada Program Menghafal Al-Qur’an di MTs Babul ‘Ulum Pajak Rambe - Hafiz Fahrurrozi Tanjung; Agusman Damanik (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The Qur'an memorization program is an important part of religious education at MTS Babul 'Ulum Pajak Rambe. Wahdah method as a learning approach that emphasizes understanding, appreciation, and consistency in memorizing the Qur'an is implemented to improve students' ability to memorize and maintain learning motivation. The formulation of the problem in this study is how the implementation of the Wahdah method in the Qur'an memorization program at MTS Babul 'Ulum Pajak Rambe. The purpose of this study is to describe the implementation of the Wahdah method and its impact on student success in memorizing the Qur'an. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results showed that the Wahdah method was implemented systematically with various techniques such as repetition, mental coaching, and prayer habituation, which significantly improved students' memorization and discipline. In conclusion, the implementation of the Wahdah method in the Qur'an memorization program at MTS Babul 'Ulum is effective in shaping students' religious character and memorization achievement.